In vitro efficacy of synthetic lawsone derivative disinfectant solution on removing dual-species biofilms and effect on acrylic denture surface properties - Jutharat Manuschai; Luelak Lomlim; Pichayaporn Ratti; Jiraporn Kara; Supawadee Naorungroj (Scientific Reports, 2023)
Abstract Candida albicans (C. albicans) and Streptococcus mutans (S. mutans) biofilms involve in denture stomatitis. This study compared compound 1 to 2% chlorhexidine gluconate (CHX), Polident, and distilled water (DW) in biofilms reduction and effect on polymethylmethacrylate acrylic (PMMA) properties. The structure of lawsone (naphthoquinone derivative) was modified by the addition of an alkylnyloxy group to yield compound 1. Dual-species biofilms of C. albicans and S. mutans were developed on PMMA discs. The colony-forming unit count measured the number of residual biofilm cells after exposure to the test agents. PMMA discs were examined for color stability, surface roughness, hardness, and chemical structure after 28 days. At 3 min, compound 1 was less effective than CHX in reducing C. albicans (p = 0.004) and S. mutans (p = 0.034) but more effective than Polident in reducing C. albicans (p = 0.001). At 15 min, no viable cells were detectable for compound 1 and its effectiveness was comparable to CHX (p = 0.365). SEM showed fungal cell surface damages in CHX, compound 1 and Polident groups. Only color change was affected by time (p < 0.001) and type of test agent (p = 0.008), and only CHX reached a clinical perception level. Compound 1 is a promising agent for removing biofilm from the PMMA surface without substantially degrading surface properties.